SEKOLAH ISLAM ELIT DAN UNGGUL (Kajian Historis dan Perkembangannya) - Ahmad Hanif Fahruddin; Ahmad Suyuthi (Akademika, 2017)
In the early 1990s, several Islamic schools began to declare themselves as elite and excellent Islamic schools. Excellent Islamic schools provide a new paradigm in the history of Islamic education in this country. Islamic education which was initially only oriented to the interests of the ukhrawi, has now begun to touch worldly aspects and began to position the fields of science and technology at a strategic level. The first excellent Islamic school was the al-Azhar and then followed by the al-Izhar in Pondok Labu Jakarta, Cendikia Senior High School Serpong, Madania High School in Parung, LPI Sabilillah Malang, and MI Murni Sunan Drajat Lamongan. To see the quality of excellent or high-quality schools, schools must achieve a minimum of National Education Standards which include: 1. Graduates Competency Standards; 2. Content Standards; 3. Educators and Education Personnel Standards; 4. Process Standards; 5. Facilities and Infrastructure Standards; 6. Financing Standards; 7. Management Standards; 8. Educational Assessment Standards. This is the minimum requirement for becoming a quality or excellent school, when the National Education Standards have been met, the quality standards of education can be carried out in the form of: a. Quality standards based on local excellence b. Quality standards that adopt or adapt international curriculum standards, or other quality standards.Keywords: Islamic, elite, excellent schools